Attrition and product layer development of limestone during simultaneous calcination and sulfation in a fluidized bed reactor. (1st June 2021) - Li, Dongfang; Ke, Xiwei; Kim, Minwoo; Cai, Runxia; Yang, Hairui; Zhang, Man; Jeon, Chung-hwan
Highlights: Sulfation was inhibited under simultaneous calcination and sulfation condition. Calcination was impeded due to product formation of CaSO4 . Product layer thickness during regime change was found to be approximately 0.7 μm. Outward development but non-uniform distribution of product layer was observed. Mercury porosimeter is more appropriate than BET for pore structure measurement. Abstract: This study investigated the physical and chemical characteristics of a Korean limestone used in a large-scale CFB boiler under simultaneous calcination and sulfation conditions in a laboratory-scale fluidized bed reactor. The conversion rate and maximum conversion degree of sulfation under simultaneous conditions were found to be lower than those under subsequent calcination and sulfation conditions. The development of the product layer during sulfation impedes the calcination reaction and results in a lower pore growth rate, which leads to a reduction in the available reaction surface area for the sulfation reaction. The simultaneous pore growth of calcination and product layer development of sulfation eventually lead to a lower rate and reduction in the maximum conversion degrees of both calcination and sulfation. Under simultaneous conditions, the elutriation rate is found to be higher than that under subsequent conditions; this is attributed to the inhibited calcination and sulfation under simultaneous conditions. To investigate the development of the product layer, the microstructure of limestone particles was studied via a scanning electron microscope coupled with an energy-dispersive X-ray analyzer. This paper reports the characteristics of the product layer development during the different sulfation reaction regimes that were found to be significant for understanding the characteristics of both the conversion degree and elutriation rate. The findings of this work can provide an insight into the physical and chemical behaviors of limestone under simultaneous conditions in a fluidized bed reactor to better comprehend the mechanism of desulfurization in CFB boilers.